Analysis of the Optic Disc and Peripapillary Structures in Monozygotic Twins. Issue 11 (November 2019) - Park, Do Young; Han, Jong Chul; Lee, Eun Jung; Kee, Changwon
Abstract : Purpose: We assessed the structural similarity of the optic disc and peripapillary region between monozygotic (MZ) twin pairs. Through these analyses, we sought to determine whether these structures are more likely to be affected by genetic or environmental factors. Methods: Using fundus photographs of 362 MZ twins, cup-to-disc ratio, tilt ratio of the optic disc, and the angle between the major temporal retinal vessels were measured. We also checked for the presence of peripapillary atrophy (PPA) and, if present, recorded its size and direction. We compared the level of consistency of these parameters and axial length (AL) between the right and left eyes within each individual and also between the corresponding paired eyes of the twins. Subgroup analysis was performed according to age and the difference in the AL between the twin pairs. Results: The mean (SD) age of the twins included in this study was 38.6 years (8.1). The size of the PPA was significantly correlated with the AL, but not with the intraocular pressure. For PPA-related factors, the level of consistency was weaker between corresponding paired eyes of the twins than between the right and left eyes within each individual. The level of consistency of the AL was the strongest in both comparisons. The level of consistency of both PPA-related factors and tilt ratio between the corresponding paired eyes of the twins was weaker in the group with a larger intertwin difference of AL than in the group with a smaller difference. Subgroup analyses by age (older age group, 45.3±6.3 y; younger age group, 32.4±2.7 y) showed that the level of consistency of PPA-related factors was weaker in the older age group than in the younger age group, after adjusting the AL. Conclusions: Unlike AL and cup-to-disc ratio, similarity of PPA between MZ twins decreased with age, suggesting that PPA could be formed as a result of various factors in addition to genetic ones. Abstract : Supplemental Digital Content is available in the text.